PDP (Perlindungan Data Pribadi) dan UU ITE - Arnold Ropen Sinaga; Acep Handra; Pramudya Adi Wiguno (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2026)
In the digital era, personal data protection has become crucial, as personal information such as names, addresses, and other details can be easily misused if not properly safeguarded. The 2020 data breach incidents on e-commerce platforms and social media in Indonesia highlighted the vulnerability of personal data. To address this issue, the Indonesian Electronic Information and Transactions Law (UU ITE) regulates personal data protection and imposes legal penalties on violators. Despite existing regulations, breaches of personal data remain frequent, indicating the need to raise public awareness about the importance of data protection. This program aims to educate the students of SMP Santa Maria Bandung about personal data protection and the UU ITE. As young individuals who are active digital technology users, students need to be equipped with proper knowledge to avoid the negative impacts of data misuse.